Influencia de Trichoderma spp, frente a desafíos fúngicos en agricultura orgánica - Mendoza Vera, Julexi Teresa (2021)
Due to the improvements that occur in the development of organic agriculture in order to eradicate toxic, resistant or residual products, the present investigation is carried out to know the importance of the genus Trichoderma in order to persuade the use of this fungus that it is favorable for the control of other existing pathogenic fungi species, which impair plant development. For the research work, bibliographic information was consulted in scientific journals, web pages, scientific articles, digital books using reference sources such as Google scholar or Google academic, also in reliable sources such as research articles. This fungus has the facility to prevent the reproduction of others, due to the toxic enzymes that it secretes, these enzymes weaken the hyphae of the pathogens and prevent them from proliferating, likewise they absorb the nutrients found in the matter that occurs in organic decomposition, making multiplication more efficient and effective. In addition, it has properties that benefit the seedlings of the crop at the time of transplantation, generating greater root growth and good absorption of nutrients. Fungi are heterotrophs that for their multiplication it is only required to be able to capture them in our environment or looking for alternatives in laboratories to multiply them and incorporate them into the soil or where the plantation that is to be protected is located, it is also easy to find them in decomposed leaves or obtaining strains of these microorganisms, it is manifested that at present means are being used to recover the microfauna, which causes that to generate an impact towards the organic.